Risk factors for hypothyroidism in euthyroid thyroid nodule patients with lymphocytic thyroiditis on fine needle aspiration cytology - Lee, Jeong-Min; Ha, Jeonghoon; Jo, Kwanhoon; Lim, Yejee; Kim, Min-Hee; Jung, Chan-Kwan; Jung, So-Lyung; Kang, Moo-Il; Cha, Bong-Yun; Lim, Dong-Jun (The Korean journal of internal medicine, 2019)
Lymphocytic thyroiditis as cytology diagnosis from fine needle aspiration (FNA) is frequently detected in patients with thyroid nodules. However, the clinical outcome for upcoming hypothyroid events has been rarely clarified in euthyroid patients. We retrospectively reviewed the data of patient who had lymphocytic thyroitidis on FNA cytology of thyroid nodule from January 2005 to December 2010 at a tertiary referral hospital. In total, 109 patients with follow-up thyroid function tests (TFT) were enrolled. Final outcomes included overt and subclinical hypothyroidism with thyroid stimulating hormone (TSH) levels ≥ 10 mIU/L. Potential parameters predicting clinical hypothyroidism were analyzed by multivariate analysis. Over the mean follow-up duration of 51.6 months, 14 out of 109 patients (12.8%) developed clinical hypothyroidism that required thyroid hormone replacement. The median onset time to hypothyroidism was 16 months (range, 3 to 88) and ≥ 60% of patients experienced clinical hypothyroidism within 1 year. By multivariate analysis, background thyroiditis (relative risk [RR], 9.78; p = 0.004), thyroid peroxidase antibody positivity (RR, 9.90; p = 0.003), nodule size (RR, 1.24; p < 0.001), and initial TSH (RR, 1.47; p = 0.009) were the independent risk factors for predicting hypothyroidism in euthyroid patients. Hypothyroidism frequently occurs during the follow-up in euthyroid patients with thyroid nodules which show lymphocytic thyroiditis on FNA cytology. Close surveillance and regular TFT are needed in high-risk patients for upcoming clinical hypothyroidism.